Attitudes and identities in learning English and Chinese as a lingua franca: a bilingual learners' perspective. Issue 9 (21st October 2018) - Chan, Jim Yee Him
ABSTRACT: With increasing global demand for English and Chinese language education, the existence of linguistic variation in (and varieties of) both languages has focused scholarly attention on the choice of language standards, norms and models. Using in-depth focus group interviews, this study compared bilingual learners' choice of English and Putonghua learning targets and examined their language attitudes and identities in relation to these two 'big' languages, both of which have played important roles in colonial and post-colonial Hong Kong. The findings revealed that the participants held a hierarchical attitude (i.e. native speaker ideology) towards English but not Putonghua, and identified four key factors affecting their choice of language learning targets, namely (1) the language's status and instrumental value, (2) the perceived attainability of the target, (3) practical communication needs and (4) the learner's cultural identity. These results shed light on the local and global status of the two languages and subsequently on the identity construction of Hong Kong people. By comparing the attitudinal patterns of learners towards the world's two 'big' languages, this paper argues for the possibility of applying a World Englishes-oriented framework to the study of Chinese, given its increasing global visibility, linguistic variation and extensive use around the world.